Imaging of PbWO4 crystals for G experiment test masses using a laser interferometer. (18th August 2022) - Assumin-Gyimah, K T A; Holt, M G; Dutta, D; Snow, W M
Abstract: It is highly desirable for future measurements of Newton's gravitational constant G to use test/source masses that allow nondestructive, quantitative internal density gradient measurements. High density optically transparent materials are ideally suited for this purpose since their density gradient can be measured with laser interferometry, and they allow in-situ optical metrology methods for the critical distance measurements often needed in a G apparatus. We present an upper bound on possible internal density gradients in lead tungstate (PbWO4 ) crystals determined using a laser interferometer. We placed an upper bound on the fractional atomic density gradient in two PbWO4 test crystals of 1 ρ d ρ d x < 2.1 × 1 0 − 8 cm −1 . This value is more than two orders of magnitude smaller than what is required for G measurements. They are also consistent with but more sensitive than a recently reported measurements of the same samples, using neutron interferometry. These results indicate that PbWO4 crystals are well suited to be used as test masses in G experiments. Future measurements of internal density gradients of test masses used for measurements of G can now be conducted non-destructively for a wide range of possible test masses.